The net of Nubian core and foldability: an attempt to individualize the lithic technology in the Palaeolithic - Beshkani, Amir (Proceedings of the Seminar for Arabian Studies, 2020)
The classic Nubian core relies on a particular volumetric configuration and is seen as a regional variant of the preferential Levallois method. This study proposes a deeper reading of Nubian technology per se and examines the Nubian structures. It is proposed that to understand Nubian technology, the rigorous definition of Nubian attributes, notably the direction of removals, must be interlinked with its fundamental geometric matrices. In this regard I have provided the net of Nubian structure in order to reveal its foldability potential in structural evolutionary pathways.